1994
DOI: 10.1111/j.1432-1033.1994.tb19910.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐shock proteins as molecular chaperones

Abstract: Functional proteins within cells are normally present in their native, completely folded form. However, vital processes of protein biogenesis such as protein synthesis and translocation of proteins into intracellular compartments require the protein to exist temporarily in an unfolded or partially folded conformation. As a consequence, regions buried when a polypeptide is in its native conformation become exposed and interact with other proteins causing protein aggregation which is deleterious to the cell. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
221
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 483 publications
(230 citation statements)
references
References 195 publications
3
221
0
1
Order By: Relevance
“…It is well established that protein aggregation has the potential to contribute to immunogenicity 21. Furthermore, the principal function of HSPs is to mediate the correct folding of proteins inside the cell and therefore, by nature, they bind to partially unfolded proteins 20. We also noted that the ability of HSPs to enhance the immunogenicity of a co‐administered antigen is well‐documented, with the successful use of HSPs in vaccine development 15.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is well established that protein aggregation has the potential to contribute to immunogenicity 21. Furthermore, the principal function of HSPs is to mediate the correct folding of proteins inside the cell and therefore, by nature, they bind to partially unfolded proteins 20. We also noted that the ability of HSPs to enhance the immunogenicity of a co‐administered antigen is well‐documented, with the successful use of HSPs in vaccine development 15.…”
Section: Discussionmentioning
confidence: 95%
“…The impact of these HCPs on immunogenicity was not explored; however, within the 20 most abundant E. coli cell proteins in the preparation, three HSPs were identified: the 60 000 MW chaperonin GroEL, the chaperone ClpB and the 70 000 MW HSP DnaK. One of the key functions of HSPs is to bind hydrophobic regions on unfolded proteins to prevent aggregation and facilitate protein folding 20. As aggregates consist of partially unfolded proteins with exposed hydrophobic regions, it would be anticipated that HSPs are likely to bind with high affinity to these regions.…”
Section: Introductionmentioning
confidence: 99%
“…The HSP70 chaperone family, including SSA1/SSA2 and SSB1/SSB2 proteins, has been extensively studied in terms of evolutionary similarity 14, 15, 16 and functional similarity/redundancy via knock‐out models 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27. For example, Craig et al.…”
Section: Introductionmentioning
confidence: 99%
“…Cold shock-induced proteins (Csps) have been well studied in Escherichia coli (Goldstein et al, 1990;Jones and Inouye, 1994;Jones et al, 1996). In contrast to hsps which are protein chaperones to help to refold the non-native proteins, prevent their aggregation or direct protein degradation (review in Becker and Craig, 1994), Csps have been shown to be RNA chaperones to prevent the formation of secondary structures in RNA at low temperature (Jones et al, 1996;Jiang et al, 1997). To our knowledge, cold shock proteins have not yet been found in human cells, thus, the e ects of cold shock on mammalian cells are poorly documented.…”
mentioning
confidence: 99%